Interfacial engineering of ZnO–PVP nanofluids: Molecular mechanisms and enhanced thermal transport for energy-efficient systems - Azocar-Guzman, M; Azocar-Guzman, M (Elsevier B.V., 2026)
ZnO/water nanofluids were engineered through dual surface functionalization with polyvinylpyrrolidone (PVP) and citric acid to achieve enhanced thermal performance at low nanoparticle loadings. At a concentration of 0.5 wt%, the ZnO–PVP nanofluid exhibited a maximum thermal conductivity enhancement of 21.17 % at 308.25 K relative to deionized water, while viscosity increases remained below 7 % over the temperature range 298.15–318.15 K. The resulting thermo-hydraulic performance index, ( k ∕ k 0)∕( μ ∕ μ 0) ≈ 1.15, indicates a net performance gain under conditions relevant to energy-efficient heat transfer applications. The magnitude of the thermal conductivity enhancement clearly exceeded the experimental uncertainty (relative error < 1.5 %), confirming the robustness of the results. Although thermal boundary conductance was not directly measured, the observed trends are consistent with an interfacial transport-dominated mechanism enabled by surface functionalization. These findings demonstrate that interfacial engineering allows the development of stable, low-viscosity, and thermally efficient ZnO-based nanofluids suitable for low-Reynolds-number thermal management systems. © © 2026. Published by Elsevier B.V.